2017
DOI: 10.1007/s11010-017-3050-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic lectins from Cephalosporium curvulum (CSL) and Aspergillus oryzae (AOL) mediate host–pathogen interactions leading to mycotic keratitis

Abstract: A core-fucose-specific lectin, CSL from Cephalosporium curvulum, has been reported earlier. Here we assign the role for CSL and another lectin AOL, from pathogenic fungus Aspergillus oryzae, in causing mycotic keratitis. CSL and AOL show strong binding to immortalized and primary human corneal epithelial cells (HCECs) which are inhibited by asialofetuin, confirming their glycan-mediated binding. CSL and AOL showed increase in viability at lower concentrations (0.07 µg/ml) whereas at higher concentrations (0.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Mycotoxins can be produced to promote fungal survival in the host [ 33 ]. Lectins can inhibit host cell growth and weaken the physical integrity of epithelial cells [ 34 ]. Consequently, early elimination of the hyphae present in the corneal tissue is critical to the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins can be produced to promote fungal survival in the host [ 33 ]. Lectins can inhibit host cell growth and weaken the physical integrity of epithelial cells [ 34 ]. Consequently, early elimination of the hyphae present in the corneal tissue is critical to the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…produce acidic, neutral, and carboxyl proteases, which increase the invasive ability of a fungus [ 42 ]. Lectines in their turn suppress the growth of the corneal cells and destroy the cellular structure of the epithelium [ 43 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…A number of interactions with host cells are known to lead to pathogen internalization, but the studies describing this invasion process remain scarce ( 41 ). Studies in corneal epithelium have revealed that Cephalosporium curvulum and Aspergillus oryzae use fucose-specific lectins to gain access to the host cell surface and, subsequently, promote infection and disease ( 42 ). It is worth noting here that a significant number of terminal and core fucose structures are present in the differentiated corneal epithelial glycocalyx, which could facilitate this type of interaction ( 43 ).…”
Section: The Glycocalyx In Ocular Surface Infectionmentioning
confidence: 99%